MENUMBUHKAN RASA INGIN TAHU ANAK DALAM KEGIATAN SAINS MELALUI MODEL PEMBELAJARAN PROBLEM BASED LEARNING - Rizkita, Diantifani; Nurcahyani, Ratna Dwi; Musfita, Regita; Azhar, Aghnia Farrassyania (IKIP Siliwangi, 2024)
Problem based learning model (PBL) has been implemented in the learning process in PAUD. The application of PBL in learning activities is carried out to develop children's abilities in identifying and finding solutions to problems that children are facing, such as in science play activities. One of the problems that occurs is related to the development of curiosity , especially those related to the ability to analyze and develop initiatives to describe problems faced by children when playing. This study was conducted to determine the extent to which the use of PBL learning models based on science activities can be used to develop the curiosity of children aged 4- 5 years in Kindergarten 'LSUPI' totaling 30 children. Data collection was carried out by using triangulation techniques in the form of observation, interviews and documentation studies , resulting in qualitative descriptive analysis techniques in the form of percentages and explanations . As a result, it is known that the application of the learning model PBL based on science activities is a tool for children to encourage and grow 8 indicators of curiosity when carrying out learning activities.